2014
DOI: 10.1007/s13277-014-2799-7
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of bevacizumab combined with chemotherapy in treatment of HER2-negative metastatic breast cancer: a meta-analysis based on published phase III trials

Abstract: Bevacizumab (Bev) combined with chemotherapy significantly improves progression-free survival (PFS) but not overall survival (OS) in patients with human epidermal growth factor receptor 2 (HER2)-negative metastatic breast cancer (MBC). The efficacy and safety depend on the type of chemotherapy combined with Bev. We performed a meta-analysis of phase III trials to evaluate the efficacy and safety of Bev + standard chemotherapy for HER2-negative MBC. The Cochrane Central Register of Controlled Trials, the Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Notwithstanding the lack of clear OS benefit, randomized trials and several metanalyses confirmed the advantage of BM in RR and PFS for patients with MBC (Valachis et al, ; Rossari et al, ; Miles et al, ; Kümler et al, ; Fang et al, ; Li et al, ), and its use in combination with taxanes is considered a promising strategy in HER2‐negative MBC.…”
mentioning
confidence: 99%
“…Notwithstanding the lack of clear OS benefit, randomized trials and several metanalyses confirmed the advantage of BM in RR and PFS for patients with MBC (Valachis et al, ; Rossari et al, ; Miles et al, ; Kümler et al, ; Fang et al, ; Li et al, ), and its use in combination with taxanes is considered a promising strategy in HER2‐negative MBC.…”
mentioning
confidence: 99%
“…Our findings confirmed the effectiveness of non-hormonal TTs in MBC patients with receptor positive, either HER2 or HR, disease. Findings by other studies suggested that increase in survival benefits was accompanied by increase in adverse effects [6,7,54,55], which can impact negatively the quality of life of MBC patients. Therefore, in clinical practice it is important to consider different dose adjustments and different combinations of treatment options.…”
Section: Discussionmentioning
confidence: 90%
“…All RCTs included in these reviews were also included in our analysis. For the RCTs in these reviews Jadad scores were not available for comparison [54,55].…”
Section: Discussionmentioning
confidence: 99%
“…The former 3 trials were double blinded,12,13,17 and the latter 4 studies were open label 16,1820. Of note, the E2100 trial was considered ineligible for this meta-analysis despite its inclusion in the previous reports on this topic 21,22. It recruited both HER2-negative and HER-2 positive patients, but the data were only available for the overall population rather than the HER2-negative subgroup.…”
Section: Resultsmentioning
confidence: 99%